2015
DOI: 10.21863/jcar/2015.4.1.005
|View full text |Cite
|
Sign up to set email alerts
|

Linkages between India and three ASEAN Stock Markets: A Co-integration Approach

Abstract: Today, an investor has an array of investment choices including the opportunities to approach overseas market which were unavailable a few decades ago. In literature, the integration of stock markets has been widely discussed and analyzed. This paper examines the relationship between Indian stock market and the three stock markets of the ASEAN countries viz. Indonesia, Malaysia, and Singapore. Using the daily closing prices of the indices over a period of ten years i.e. 2004 to 2014, the study examined the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Gupta and Shrivastav (2018) found significant integration between stock markets of India and Japan. Similarly, equilibrium relation was observed between India and selected developed stock markets viz., Australia, Canada, France, Germany, India, UK and USA (Samadder and Bhunia 2018). Gupta and Shrivastav (2018) also reported significant integration between stock markets of India and Japan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gupta and Shrivastav (2018) found significant integration between stock markets of India and Japan. Similarly, equilibrium relation was observed between India and selected developed stock markets viz., Australia, Canada, France, Germany, India, UK and USA (Samadder and Bhunia 2018). Gupta and Shrivastav (2018) also reported significant integration between stock markets of India and Japan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study revealed that there was a co-movement of stock prices on an international platform. Further investigation done by Rajkumar (2015) revealed that there is an integration between Indian Stock Market and 3 other markets namely Malaysia, Indonesia and Singapore. A study conducted by Umer, Sevil, and Kamişli (2015) proves that there exists the strong integration between stock prices and exchange rates of 0 emerging markets.…”
Section: Review Of Literaturementioning
confidence: 99%